2012
DOI: 10.1155/2012/614129
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Management of Mandibular Second Molar Fused to a Supernumerary Tooth, Using Spiral Computed Tomography as a Diagnostic Aid: A Case Report

Abstract: Fusion is a developmental anomaly characterized by the union of two adjacent teeth. In this paper we report a rare case of fusion involving permanent mandibular second molar with supernumerary tooth. The rarity with which this entity appears, along with its complex characteristics, often makes it difficult to treat. The use of high-end diagnostic imaging modalities such as spiral computed tomography can help the clinician in making a confirmatory diagnosis and determining the treatment plan before undertaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Especially in case of fusion between a regular tooth and a supernumerary tooth, more arch length is required causing spacing and alignment problems [ 46 ]. To our knowledge, little is known about the prevalence of maxillary second molars fusion with supernumerary teeth [ 47 ], except some case reports published over the past years, which are mainly focused on mandibular molars [ 45 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially in case of fusion between a regular tooth and a supernumerary tooth, more arch length is required causing spacing and alignment problems [ 46 ]. To our knowledge, little is known about the prevalence of maxillary second molars fusion with supernumerary teeth [ 47 ], except some case reports published over the past years, which are mainly focused on mandibular molars [ 45 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…[357] However, major anatomical variations are frequently observed in clinical practice. Tooth fusion is characterized by large clinical crowns and the presence of one pulp chamber and two root canals.…”
Section: Discussionmentioning
confidence: 99%
“…[456] Extra care should be taken in the presence of gaps that favor the accumulation of plaque and the development of dental caries. Periodontal diseases requiring multidisciplinary therapy should also be managed carefully.…”
Section: Introductionmentioning
confidence: 99%
“…25 Rudagi et al confirmed the complicated morphology of the root canal system of the double teeth with the SCT imaging prior to root canal treatment. 26 Keys et al used CBCT imaging in order to plan surgical and endodontic treatment of double teeth. 27 The authors stated that CBCT images enhanced the pretreatment information by allowing visualization of root canal morphology and adjacent anatomical structures.…”
Section: Discussionmentioning
confidence: 99%